Pelanggaran Norma Etika dan Moral dalam Kehidupan Bermasyarakat (Studi Kasus Pada Remaja di Desa Mapanget Kecamatan Talawaan Kabupaten Minahasa Utara) - Syaloom Shefia Wullur; Apeles Lexi Lonto; Julien Biringan (Tumoutou Social Science Journal, 2026)
This study aims to find out the picture of violations of ethical and moral norms in social life in adolescents and identify the factors that affect the occurrence of these violations in Mapanget Village, Talawaan District, North Minahasa Regency. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of adolescents, parents, and the village government. The results of the study show that violations of ethical and moral norms committed by adolescents include fights, abusive words to elders, disrespect for teachers and parents, making noise in the community, and other behaviors that are contrary to values, morals, and norms that apply in social life. Factors that affect the occurrence of these violations include internal factors and external factors. Internal factors include unstable emotions, lack of self-control, and a desire to be recognized by peers. Meanwhile, external factors include peer influence, poor social environment, lack of supervision from parents, and the influence of social media. Therefore, the role of the family, community, and village government is needed in providing guidance and strengthening of ethical and moral values to adolescents in order to create an orderly, safe, and harmonious social life.